ANALISIS TINGKAT KEPUASAN KONSUMEN PADA AGROINDUSTRI LEDRE SUPER MORO TRESNO BOJONEGORO - Mubarokah, Mubarokah; Firdauzi, Aulia; Fitriana, Nisa Hafi Idhoh (International Journal of Multidisciplinary Research and Literature, 2023)
The impact of the Covid-19 pandemic has affected the decline in sales of agroindustries, including the Super Moro Tresno Ledre agroindustry. It can be seen from the decrease in the Number of tourists in Bojonegoro Regency in the last two years (2020-2021), which has an impact on the sale of ledre as a typical souvenir food from Bojonegoro has decreased consumers. In addition, the development of ledre agroindustry in Bojonegoro is quite a lot, which certainly causes competition among fellow ledre agroindustries. This research aims to analyze the level of customer satisfaction and the attributes that need to be improved to increase customer satisfaction. This research uses the Customer Satisfaction Index (CSI) method for the first objective and the Importance Performance Analysis (IPA) method for the second. The results showed that the overall level of customer satisfaction based on the CSI value was 75.67%, which means that customer satisfaction is in the "Satisfied" index. Based on the results of the IPA analysis, it is known that several attributes need to be improved, which include product packaging standards, responses to consumer complaints and suggestions, varied and affordable prices, suitability of packaging portions at the cost spent, prices offered with the benefits obtained by consumers, freedom of movement in the store, and shop space arrangement